Increased exacerbations and hospitalizations among PI*MZ compared to PI*MM individuals: an electronic health record analysis - Vickram Tejwani; Yifan Wang; Lauren Munoz Tremblay; Elizabeth Azzato; Arianne K. Baldomero; Christine Wendt; Amy Attaway; Russell Bowler; Umur Hatipoglu; Rebecca Hutton; Charlie Strange; Xiaofeng Wang; et al. (Respiratory Research)
Abstract Background The best described endotype of COPD is alpha-1 antitrypsin (AAT) deficiency, due to a genetic abnormality in the SERPINA1 gene. Common deficient PI variants are the Z and S variants. Homozygotes for the Z allele (PI*ZZ individuals) carry the genotype most commonly associated with severe AAT deficiency (AATD), but a highly prevalent endotype is the heterozygous state (PI*MZ individuals). The effect of PI*MZ status on exacerbations and health care utilization is unknown. Study design and methods Cleveland electronic health record data was examined to compare healthcare utilization between PI*MZ and PI*MM individuals. Three outcomes were assessed: moderate COPD exacerbation (defined as short-term steroid prescription), any emergent care (defined as an express care, urgent care, or emergency department visit), and any hospitalization. Models were adjusted for age, sex, race, BMI, smoking status, comorbidity count, liver disease, zip code median income. Results 4,148 individuals had the PI*MM genotype and 308 PI*MZ. PI*MZ was associated with increased risk for moderate COPD exacerbations (HR [95% CI]: 1.66 [1.27, 2.17]) and hospitalizations (HR [95% CI]: 1.44 [1.19, 1.75]) compared to PI*MM. The risk of hospitalization was higher among PI*MZ individuals with AAT levels < 90 mg/dL (HR [95% CI]: 1.59 [1.14, 2.23]) but not in those with AAT levels > 90 mg/dL, as compared to PI*MM. Interpretation Given the high prevalence, PI*MZ represents a COPD phenotype that is associated with worse outcomes, inviting additional investigation to identify predictive biomarkers of worse disease and treatable traits. Future prospective studies to better characterize the longitudinal course and healthcare utilization among individuals with a PI*MZ genotype.